THE ICONOGRAPHY OF LORD BHAIRAVA IN LITERARY SOURCES - Sokhi, Simer Preet (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper delves into the captivating realm of Lord Bhairava’s iconography as portrayed in literary sources. Despite the immense power and significance of Lord Bhairava, he often resides in the shadows cast by the more widely recognized deity, Lord Shiva. Consequently, the visual representation of Lord Bhairava, characterized by its richness and intricacy, has been relatively neglected in scholarly investigations. By closely examining various literary references, this study endeavors to unravel the multifaceted aspects of Lord Bhairava’s iconography, including his distinctive features, diverse forms, captivating myths, and legendary tales. Furthermore, it aims to dispel prevailing misconceptions and kindle awareness about the nature of this fierce and enigmatic deity. Employing a comprehensive analysis of literary iconography, this research illuminates the unique attributes and profound significance that Lord Bhairava holds within the realm of mythology and religious art. Through an exploration of the nuances and symbolism embedded within his depictions, this study contributes to a deeper understanding and appreciation of Lord Bhairava’s representation and its broader cultural implications.